2009
DOI: 10.1303/aez.2009.301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pollination by Melipona quadrifasciata (Hymenoptera: Apidae) on tomatoes in protected culture

Abstract: To evaluate the pollination efficiency of a stingless bee, Melipona quadrifasciata, individuals originating from tropical and subtropical regions of South America were examined on tomatoes (cv. Momotaro 8) cultivated in a greenhouse in summer and autumn. We compared differences in the rates of foraged flowers, pollen weights foraged from anthers, rates of fruit set of tomatoes, seed number of tomato fruits and yields of tomato fruit weight between M. quadrifasciata and the bumblebee, Bombus terrestris. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Environmental factors, including temperature may also affect the capacity of bees to deliver pollination services. For instance, the buzz-pollinating stingless bee, Melipona quadrifasciata Le Peletier (Hymenoptera: Apidae), is thought to be an efficient tomato pollinator only when temperatures do not go above 28°C ( Hikawa and Miyanaga 2009 ). An additional factor that could explain the varying effects of a single pollination treatment on tomato fruit weight that we observed is variation in visitation rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental factors, including temperature may also affect the capacity of bees to deliver pollination services. For instance, the buzz-pollinating stingless bee, Melipona quadrifasciata Le Peletier (Hymenoptera: Apidae), is thought to be an efficient tomato pollinator only when temperatures do not go above 28°C ( Hikawa and Miyanaga 2009 ). An additional factor that could explain the varying effects of a single pollination treatment on tomato fruit weight that we observed is variation in visitation rates.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially reared native bees produced on a mass scale with low genetic diversity could still increase the spread of bee pathogens, as well as influence genetic diversity of their wild counterpart if/when they interact with native bees during foraging or mating ( Hikawa and Miyanaga 2009 ). To circumvent these problems, Hikawa and Miyanaga (2009) suggest a radical new strategy: importing Melipona stingless bees from the neotropics for tomato pollination in Japan. Melipona bees are found throughout the warm areas of the Neotropics and colonies have been cultivated by humans for over 3,000 yr in Mesoamerica ( Quezada-Euán 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stingless bees present great potential to be used in commercial crop pollination 7,44,45 . Indeed, Melipona bees have been demonstrated to be efficient pollinators of many economically important fruits and vegetables including tomatoes [46][47][48][49] , eggplant 9 , sweet pepper 50 and annatto 51 . A recent study using the RFID technology with the stingless bee M. fasciculata showed that workers of this species can forage up to a distance of 10 km away from their hives 52 , suggesting that these bees are well suited for pollination of large scale plantations as well.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the number of studies involving the management of pollinators in greenhouses has grown steadily in recent years. Among tomato pollinators in greenhouses are Amegilla chlorocyanea (Cockerell) (Hogendoorn et al, 2006), bees of the genus Xylocopa (Lestis) Lepeletier & Serville (Hogendoorn et al, 2000) and Bombus Latreille (Morandin et al, 2001), and the stingless bees N. perilampoides (Cauich et al, 2004;Palma et al, 2008) and M. quadrifasciata (Del Sarto et al, 2005;Bispo dos Santos et al, 2009;Hikawa & Miyanaga, 2009). Stingless bees are particularly promising for use as commercial pollinators (Cruz & Campos, 2009), given that they do not present a functional sting, are easy to handle (usually low aggressive-nonstinging), have populous and perennial nests, present a marked worker recruitment behavior and stock a large amount of food (Heard, 1999).…”
Section: Research Article -Beesmentioning
confidence: 99%